Development and validation of a menstruation-related activity restriction questionnaire among adolescent girls in urban resettlement colonies of Delhi - Suneela Garg; Yamini Marimuthu; Nidhi Bhatnagar; M Megha Chandra Singh; Amod Borle; Saurav Basu; Falak Azmi; Yomri Dabi; Indu Bala (Wolters Kluwer Medknow Publications, 2021)
Introduction: Menstruation, a physiological phenomenon, till date is associated with myths, taboos, and malpractices. These interfere with the emotional, physical, and mental health of adolescent girls. This study attempts to draft a validated questionnaire to measure menstruation-related activity restriction. Objective: The objective was to study activities restricted during menstruation among adolescent girls residing in urban resettlement colonies of Delhi and to develop and validate a questionnaire for menstruation-related activity restriction. Materials and Methods: A community-based cross-sectional study was conducted among adolescent girls residing in urban resettlement colonies of Delhi during 2019. A multistage random sampling technique was used to select 1100 girls across four districts of Delhi. A 15-item questionnaire was developed by an expert committee and validated with principal component analysis (PCA). Results: In total, 1100 adolescent girls were included in the study whose mean age was 15.8 (±2.1) years. School/college/work was missed due to menstruation in 60% of the adolescent girls, 66% were not comfortable during menstruation, and 92% were restricted from entering religious places. In exploratory factor analysis using PCA, 6 principal components were identified which had eigenvalues more than 1. Conclusion: Religious restrictions during menstruation (94%) were highly prevalent among adolescent girls, followed by restriction of routine activity (69%) and work/academically related activity (60%). Construct validity has identified a six-factor structure for the menstruation-related activity restriction questionnaire. This was identified as a valid and internally consistent tool to assess activities restricted during menstruation among Indian adolescent girls.